Investigations into Luminescent Properties of Sm(III), Eu(III), Tb(III) and Dy(III) Complexes of Some Schiff-base Ligands - Shakya, Pawan Raj; Tamrakar, Cirika Shova (Journal of Institute of Science and Technology, 2015)
Luminescent properties of Sm(III), Eu(III), Tb(III) and Dy(III) complexes of three Schiff-base ligands viz., H2L1, H2L1 and H2L3 [where H2L1 = N,N’-di-(4-decyloxysalicylidene)-1’,4’-diaminobutane; H2L2 = N,N’-di-(4-decyloxysalicylidene)- 2’,6’-diaminopyridine; and H2L3 = N,N’-di-(4-decyloxysalicylidene)-1’,3’-diaminobenzene] synthesized in our earlier work were investigated. The homo dinuclear lanthanide complexes were of the type, [Ln2(LH2)3(NO3)4](NO3)2. Luminescence analysis revealed that among the lanthanide complexes, only Sm(III) complex of H2L1 was found to have displayed characteristic metal-centered emission (solution state) whereas Sm(III), Eu(III) and Tb(III) complexes of H2L1 and Eu(III) and Tb(III) complexes of H2L3 exhibited ligand-centered emissions. Journal of Institute of Science and Technology, 2014, 19(1): 19-24